Men and Manners : Essays, Advice and Considerations. - Coggins, David (Abrams, 2018)
Today's man may know how to dress with style, but does he know how to behave' Though the rules of civility have changed along with the world, Men and Manners believes in manners. This book doesn't tell you which fork to use or how to write a thank you note. But it is going to remind you of basic, respectful rules you may have forgotten or have chosen to ignore. Comprised of short essays, shorter interviews, and lists of guidelines for men of all ages, this book provides an honest, playful, and humorous look at the conflicted state of manners today. Subjects that may fluster today's man-such as tipping, toasting, texting, grooming, dating, office behavior, and home decor-are explored with the trademark combination of dry wit and self-deprecating attitude that has made David Coggins one of today's most well-respected men's style writers. With humorous illustrations and contributions from some of today's male style icons, Men and Manners makes the case for being the man who offers the best seat to his companion, who knows when to pick up the tab, and who remembers to do what's right even if it isn't always rewarded.